Spherical Polybutylene Terephtalate (PBT)-Polycarbonate (PC) Blend Particles by Mechanical Alloying and Thermal Rounding - Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Lanzl, Lydia; Drummer, Dietmar; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2018)
In this study, the feasibility of co-grinding and the subsequent thermal rounding to produce spherical polymer blend particles for selective laser sintering (SLS) is demonstrated for polybutylene terephthalate (PBT) and polycarbonate (PC). The polymers are jointly comminuted in a planetary ball mill, and the obtained product particles are rounded in a heated downer reactor. The size distribution of PBT-PC composite particles is characterized with laser diffraction particle sizing, while the shape and morphology are investigated via scanning electron microscopy (SEM). A thorough investigation and characterization of the polymer intermixing in single particles is achieved via staining techniques and Raman microscopy. Furthermore, polarized light microscopy on thin film cuts enables the visualization of polymer mixing inside the particles. Trans-esterification between PBT and PC during the process steps is investigated via vibrational spectroscopy and differential scanning calorimetry (DSC). In this way, a new process route for the production of novel polymer blend particle systems for SLS is developed and carefully analyzed.
Keywords: polybutylene terephthalate (PBT); polycarbonate (PC); polymer blend particles; spheroidization; additive manufacturing; Raman microscopy; SEM staining; trans-esterification